2014
DOI: 10.1017/s002221511400259x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for recurrence of peritonsillar abscess

Abstract: Our results suggest that tonsillectomy may be indicated as a treatment for peritonsillar abscess in patients with a history of recurrent tonsillitis or extraperitonsillar spread on computed tomography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 23 publications
0
24
0
2
Order By: Relevance
“…There exists a plethora of potential reasons for persistent or recurrent peritonsillar disease. Early recurrences, or persistence of disease, could be related to inadequate treatment (such as inadequate drainage of the peritonsillar space), extraperitonsillar spread of infection, or autoimmune deficiency . Later recurrences could be related to autoimmune deficiency or prior history of tonsillitis or pharyngitis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There exists a plethora of potential reasons for persistent or recurrent peritonsillar disease. Early recurrences, or persistence of disease, could be related to inadequate treatment (such as inadequate drainage of the peritonsillar space), extraperitonsillar spread of infection, or autoimmune deficiency . Later recurrences could be related to autoimmune deficiency or prior history of tonsillitis or pharyngitis.…”
Section: Discussionmentioning
confidence: 99%
“…Although less common in contemporary times, surgical drainage or performance of quinsy tonsillectomy is occasionally performed for urgent evacuation of purulence in select patients . Persistent disease or development of a recurrent abscess can be common, with studies describing recurrence rates ranging from 9.6% to 40% …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systemic complications include sepsis and jugular vein thrombophlebitis [4]. In a study involving 172 patients with PTA, Chung et al found that extraperitonsillar spread of infection and recurrent episodes of tonsillitis were significant predictors of PTA recurrence [11]. The reported recurrence rate ranges from 5.9% to 22.7% [2].…”
Section: Discussionmentioning
confidence: 99%
“…A previous paper investigating risk factors for recurrence of peritonsillar abscess adds to these findings. 3 The contention that personal music systems used at high volume are harmful to hearing is corroborated by Kumar and Deepashree's experimental work involving 60 participants. 4 The authors found that personal music systems used at high volumes led to: elevated high frequency thresholds, reduced frequency discrimination and temporal modulation detection, and poor speech perception.…”
mentioning
confidence: 93%